Clima organizacional y su influencia en la satisfacción laboral del área de talento humano de la empresa rey banano del pacífico, “Reybanpac C.l.”, año 2022 - Salvatierra Sánchez, Ruth Bridget (2024)
The positive organizational climate is one of the fundamental bases for the good performance and administration of a company; it produces a level of satisfaction among workers, which enhances development and improves their skills. The objective of this research was to analyze the organizational climate and its influence on job satisfaction in the Human Talent area of the company Rey Banano del Pacífico REYBANPAC CL., a company with high participation in the local labor market, more than 6,500 direct jobs., which directly affects the organizational climate. The methodology used was descriptive in nature, with a qualitative and analytical approach, and allowed taking into consideration the variables of the research topic for better understanding. They were extracted from the application of surveys, interviews and focus groups, which were organized for analysis and presentation based on the objectives. The results showed that the organizational climate directly influences the job satisfaction of employees, they also showed that 91% of workers agree with the mechanisms applied by the human talent area to motivate staff and that the company uses 3 parameters to measure possible weaknesses in job satisfaction and organizational climate. In conclusion, a positive work environment generates personal well-being in employees, which leads to job satisfaction, which is ideal for creating a healthy work environment in a way that helps achieve short- and long-term objectives.